2021
DOI: 10.1177/0974910121989458
|View full text |Cite
|
Sign up to set email alerts
|

Wage Gap Between Formal and Informal Regular Workers in India: Evidence from the National Sample Survey

Abstract: This article elucidates the wage differential between formal and informal workers across different sectors, gender, occupation, and industry by using the 61st (2004–2005) and 68th (2011–2012) Rounds of National Sample Survey Office (NSSO) unit-level data. The study emphasizes two things: first, identifying the existence of the absolute wage gap between formal and informal workers and, second, finding the intensity of discrimination in wage between formal and informal workers. The vast body of literature availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The 2017-2018 National Sample Survey (NSSO) reported that 52% of individuals were self-employed, largely in the informal sector, while 25% were employed in casual daily wage work and 23% were salaried [13]. As per the 2011-2012 NSSO, the national average daily wage rate for informal sector workers was INR 277, less than half of the daily wage rate of INR 716 in the formal sector [14]. In addition to this dependency on cheap informal labor, India also lacks social security programs that could buffer individuals from the adverse effects of financial hardship [15].…”
Section: Introductionmentioning
confidence: 99%
“…The 2017-2018 National Sample Survey (NSSO) reported that 52% of individuals were self-employed, largely in the informal sector, while 25% were employed in casual daily wage work and 23% were salaried [13]. As per the 2011-2012 NSSO, the national average daily wage rate for informal sector workers was INR 277, less than half of the daily wage rate of INR 716 in the formal sector [14]. In addition to this dependency on cheap informal labor, India also lacks social security programs that could buffer individuals from the adverse effects of financial hardship [15].…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, they found that the incidence of food insecurity was higher among lower castes, though more of this differential was explained through differences in overall identity than caste. Kumar and Pandey (2021) explained factors contributing to significant discrimination caused by lack of formal employment in India using the Threefold Blinder Oaxaca decomposition method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The trends in working age population growth and employment growth for men and women in rural and urban areas in the period between 2011-12 and 2017-18 show that the working age population grew by 115.5 million but the labour force grew only by 7.7 million and the workforce actually shrank by 11.3 million. This means there is a significant fall in the labour force participation rate 1 (LFPR) as well as workforce participation rate 2 (WPR), and a sharp rise in the unemployment rate [50].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the data of ASI, Basole & Narayan [55] indicate a rising trend in the share of contract workers in India's organized manufacturing sector and this is despite labour laws prohibiting 1 Workforce Participation Rate (WPR): WPR is defined as the percentage of employed persons in the total working age population (individuals aged 15 years and above). It is usually considered a better indicator of conditions in the labour market compared to the Unemployment Rate (UR) as UR can also fall without an increase in employment due to individuals dropping out of the labour force.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation